Les déterminants de l'activité didactique du professeur débutant en éducation physique et sportive - Fabienne Brière-Guenoun (Nantes Université, 2016)
Our research aims to describe and understand the ways in which both beginning teachers in physical education lead the advancement of knowledge in the classroom to identify the determinants of their teaching activity. Referring to studies of didactic joint action, practical epistemology of the two beginning teachers is characterized by the unique and evolving articulation of theories (about teaching, PE teaching, and learning) and personal references. It is rooted in a double report on the initial training and official requirements. And it is reconfigured under the influence of contextual determinants that ultimately guide the construction of their relation to relation to professional activity.